Hydrophilic domain II of Escherichia coli Dr fimbriae facilitates cell invasion. - Das, M; Hart-Van Tassell, A; Urvil, P; Lea, S; Pettigrew, D; Anderson, K; Samet, A; Kur, J; Matthews, S; Nowicki, S; Popov, V; Goluszko, P; et al. (2005)
Uropathogenic and diarrheal Escherichia coli strains expressing adhesins of the Dr family bind to decay-accelerating factor, invade epithelial cells, preferentially infect children and pregnant women, and may be associated with chronic or recurrent infections. Thus far, no fimbrial domain(s) that facilitates cell invasion has been identified. We used alanine scanning mutagenesis to replace selected amino acids in hydrophilic domain II of the structural fimbrial subunit DraE and evaluated recombinant mutant DraE for attachment, invasion, and intracellular compartmentalization. The mutation of amino acids V28, T31, G33, Q34, T36, and P40 of DraE reduced or abolished HeLa cell invasion but did not affect attachment. Electron micrographs showed a stepwise entry and fusion of vacuoles containing Escherichia coli mutants T36A and Q34A or corresponding beads with lysosomes, whereas vacuoles with wild-type Dr adhesin showed no fusion. Mutants T31A and Q34A, which were deficient in invasion, appeared to display a reduced capacity for clustering decay-accelerating factor. Our findings suggest that hydrophilic domain II may be involved in cell entry. These data are consistent with the interpretation that in HeLa cells the binding and invasion phenotypes of Dr fimbriae may be separated.